H2Karst research in limestone hydrogeology - Zwahlen, François; Bertrand, Catherine; LaMoreaux, James W.; Mudry, Jacques (Environmental Earth Sciences, 2014)
Chapters in this book are contributions from the 9th Conference on limestone hydrogeology, organized in Besançon in September 2011 selected by the scientific committee of H2Karst.The book presents latest results on in the field of groundwater flow and storage within the different subsystems of karst aquifers; insights into the complex interaction between groundwater and surface water in karst areas by a multidisciplinary approach; current knowledge on contamination problems and contaminant transport in karst aquifers as well as an overview of karst hydrogeology in different contexts around the world.